Sie sind auf Seite 1von 4

# Equations for a Geodesic

## A Simple Lagrangian Choice

Consider the space with metric tensor gmn , depending on the coordinates xa . The line element is then: ds2 = gmn dxm dxn (1) At this point, gmn is a symmetric matrix of real numbers. We will take this matrix to be non-singular, and write the inverse matrix in the notation g mn . It then follows that
e g ec gcm = m

(2)

e where m is the usual Kronecker delta, that is the identity matrix. We consider the Lagrangian function along a path described by xm (), where is some parameter along , to be: 2 ds (3) L= d

## so that the Lagrangian function can be written: L = gmn x mx n (4)

where x m = dxm /d is the derivative of coordinate xm along the path parameterized by . It is important to note that L is a function of both the coordinates xa through the coordinate dependence of gmn , and their derivatives x a . We now wish to derive the conditions on the path that extremizes the integral: L d (5) These conditions are described by the usual Euler-Lagrange equations: d d L x c = L xc (6)

## A Constant Along the Path

c Charles C. Dyer

Since the function L is a homogeneous quadratic function of the velocity coordinates, x , we have: L x c c = 2L. (7) x We are interested in the variation of L along the extremal path, so we consider:
a

dL L dxc L dx c = + d xc d x c d Using the Euler-Lagrange equations, this can be re-written as: dL d = d d L x c dxc c L dx d L + c = x c c d x d d x =2 dL d

(8)

(9)

from which we have the fundamental result dL = 0, so that L is constant along the extremal d path. One important consequence of this result is that the extremal path cannot change its time-like, null, or space-like character along the path.

Geodesic Equations
In N dimensions, L is a function of 2N independent variables. We then have L n m m x n x = g + x x mn x c x c x c but since
x m x c m = c , we can write:

(10)

## L m n = gmn (x n c +x m c )=x n gcn + x m gmc x c

(11)

On replacing the summation index n by m in the rst term, and using the symmetry of gmc , we have: L = 2gcm x m (12) x c Taking the total derivative of this with respect to , we have: d d L x c = 2x m dx m dgcm + 2gcm d d (13)

but since gcm depends on the coordinates xa , which have non-zero derivative wrt , we have: d L = 2gcm|b x bx m + 2gcm x m (14) d x c where the |c subscript means the partial derivative with respect to coordinate xc . Since x bx m is symmetric in b and m, we can replace 2gcm|b by gcm|b + gcb|m in the rst term, to obtain: d L = gcm|b + gcb|m x bx m + 2gcm x m (15) d x c 2

Since xa and x b are independent variables in the Euler-Lagrange equations, the following holds: L = gmn|c x mx n = gmb|c x mx b (16) xc where we have replaced n by b to get the last equality. We can then write the Euler-Lagrange equations in the form: gcm|b + gcb|m x bx m + 2gcm x m = gmb|c x mx b Re-arranging, we have: gcm x m + 1 x bx m gcm|b + gcb|m gmb|c = 0 2 (18) (17)

Multiplying by g ec and summing over c, that is contracting with g ec , and remembering that e g ec gcm = m , we then have: x e + 1 x bx m g ec gcm|b + gcb|m gmb|c = 0 2 If we now dene the Christoel symbol of the second kind 1 as:
1 ec e gcm|b + gcb|m gmb|c mb = 2 g

(19)

(20)

## we can write the geodesic equation as: x e + e mx b = 0 mb x (21)

By choosing a dierent independent variable, say (), this equation can be re-written. Any choice for () which leaves the right-hand side zero means that the parameter is an ane parameter, and the transformation is of the form = a + b where a and b are real constants. If the transformation () results in the right-hand side not being zero, the new parameter is not an ane parameter.

## Other Choices for the Lagrangian Function

We have considered the Lagrangian L = gmn x mx n (22)

= L instead, since this is but it might appear that we should have used the Lagrangian L more clearly related to the arc-length along the path. Thus it might useful to consider the Euler-Lagrange equations for the more general Lagrangian F (L), where F is some function of L along the path. We have directly that: dF L F dF L F = and = c c c x dL x x dL x c
1

(23)

We will only use the Christoel symbol of the second kind throughout, and never use the Christoel symbol of the rst kind, so we will henceforth drop the use of the words second kind.

Now

d d d d

F x c F x c

d d

dF dL

L dF d + c x dL d

L x c L x c

(24)

Then

d2 F dL L dF d + 2 c dL d x dL d

(25)

## Since dL/d vanishes along the extremal path, we have: d d F x c dF F = xc dL d d L x c L xc =0 (26)

It then follows directly that F also satises the Euler-Lagrange equations along the extremal path. As a result, our geodesic equations derived from the Euler-Lagrange equations ex tremizing our original Lagrangian function choice, L, also extremize the function L along the path.